Association Between Candidate Genes of Innate Immunity, Gallinacin Genes and Resistance to Marek’s Disease in Chicken - Yacoub, H.A.; Galal, A.; Fathi, M.M.; El Fiky, S.A.; Ramadan, H.A.I. (International Journal of Poultry Science, 2011)
Gallinacins are antimicrobial peptides that play a significant role in innate immunity in chicken. The aim of this study was to determine the relationship between gallinacin genes and resistance to Marek's disease and to predict whether the amino acids substitutions lead to produce new phenotypes. We used in current study two inbred White Leghorn Lines 6 and 7. We examined gallinacins genes (3-5 and 10) by sequenced a 2.29 kb in two directions from two inbred lines (6 and 7). A total of 10 SNPs were identified within the sequenced regions. This equates to an SNP rate of 4.36 SNPs/kb, nearly to the previously reported 5 SNPs/kb across the entire chicken genome. The current study showed that the gallinacin genes are polymorphic because there are many (SNPs) in both inbred lines of White Leghorn chickens and some of these SNPs are nonsynonymous and others are synonymous. We are concluded that a new chromosomal region with effects on the response to Marek's disease in chickens was characterized in this study. Within this region, the SNPs in the gallinacin candidate genes could potentially be used in a marker assisted selection program to enhance the response to Marek's disease. Analysis of the gallinacin genes in the protective pathways of disease resistance has also opened the possibilities for therapeutic strategies using endogenous antimicrobial peptides.